Conserved noncoding sequences and de novo Mutator insertion alleles are imprinted in maize - Li, Tong; Yin, Liangwei; Stoll, Claire E; Lisch, Damon; Zhao, Meixia (Plant physiology (Bethesda), 2023)
Genomic imprinting is an epigenetic phenomenon in which differential allele expression occurs in a parent-of-origin-dependent manner. Imprinting in plants is tightly linked to transposable elements (TEs), and it has been hypothesized that genomic imprinting may be a consequence of demethylation of TEs. Here, we performed high-throughput sequencing of ribonucleic acids from four maize (Zea mays) endosperms that segregated newly silenced Mutator (Mu) transposons and identified 110 paternally expressed imprinted genes (PEGs) and 139 maternally expressed imprinted genes (MEGs). Additionally, two potentially novel paternally suppressed MEGs are associated with de novo Mu insertions. In addition, we find evidence for parent-of-origin effects on expression of 407 conserved noncoding sequences (CNSs) in maize endosperm. The imprinted CNSs are largely localized within genic regions and near genes, but the imprinting status of the CNSs are largely independent of their associated genes. Both imprinted CNSs and PEGs have been subject to relaxed selection. However, our data suggest that although MEGs were already subject to a higher mutation rate prior to their being imprinted, imprinting may be the cause of the relaxed selection of PEGs. In addition, although DNA methylation is lower in the maternal alleles of both the maternally and paternally expressed CNSs (mat and pat CNSs), the difference between the two alleles in H3K27me3 levels was only observed in pat CNSs. Together, our findings point to the importance of both transposons and CNSs in genomic imprinting in maize.